Treating a GAD65 Antibody-Associated Limbic Encephalitis with Basiliximab: A Case Study - Widman, Guido; Golombeck, Kristin; Hautzel, Hubertus; Gross, Catharina C.; Quesada, Carlos M.; Witt, Juri-Alexander; Rota-Kops, Elena; Ermert, Johannes; Greschus, Susanne; Surges, Rainer; Helmstaedter, Christoph; Wiendl, Heinz; et al. (Frontiers in Neurology, 2015)
Background: Antibodies (ABs) against the 65 kDa isoform of the intracellular enzyme glutamate decarboxylase (GAD65) have been found in limbic encephalitis (LE) and other neurological conditions. The direct significance of anti-GAD65-ABs for epilepsy is unclear. However, in histological preparations from biopsies of resective epilepsy surgeries, predominantly cytotoxic T-lymphocytes were detected making close contacts to neurons. Activated T-lymphocytes can, in turn, be selectively controlled by therapeutic interleukin-2 receptor ABs such as Basiliximab. Case Presentation: We report of a 25 year-old male patient with epilepsy since the age of 18 and displaying clinical signs of LE and a high titer of GAD65 ABs in cerebrospinal fluid (CSF) and serum. Monthly, repetitive, intravenous Cortisone pulse therapies that were initially administered for six months failed to improve his condition. Subsequent flow-cytometry analysis of CSF showed especially an increased fraction of activated HLADR+ CD8+ T-Lymphocytes (fCD8+TL) when compared to controls. Thus, a second, intravenous Cortisone pulse therapy with an additional Basiliximab dose of 20mg/month was started. After three months, the fCD8+TL in the CSF normalized; after six months, the psychological impulse-control deficits normalized; and after eleven months the patient was seizure free. However, seven weeks later, seizures and, later on, psychological deficits recurred and fCD8+TL were once again present in the CSF. Flumazenil-PET, MRI-volumetry and neuropsychological changes during therapy are described. Conclusion: The correlation of the fCD8+TL in the CSF with clinical and paraclinical measures of disease activity combined with the unambiguous response to Basiliximab strongly argues in favor of the putative pathogenic role fCD8+TL in anti-GAD65 LE. The clinical relapse at the end of the observation period might be due to the formation of human anti-drug ABs, a well-known complication of therapy with chimeric ABs.